Micro-osteoperforations and Its Effect on the Rate of Tooth Movement: A Systematic Review - Al-Khalifa, Khalifa S. (Eur J Dent, 2021)
Prolonged orthodontic treatments have inconvenienced patients and clinicians alike. Surgically assisted techniques for accelerating orthodontic tooth movement have shown promising results in the literature over the years. The minimally invasive nature of micro-osteoperforations (MOPs), however, for enhanced orthodontic tooth movement has recently gained momentum, with many clinical trials conducted on both animals and humans. An electronic search was performed to extract papers using PubMed, Google Scholar, Scopus, and Web of Science. The keywords that were used included “MOP,” “accelerating tooth movement,” “orthodontic tooth movement,” and “regional acceleratory phenomenon.” The studies that met our inclusion criteria were extracted and evaluated in this review. MOPs have been proven time and again, in animal and human studies alike, to increase the rate of orthodontic tooth movement. The application of perforations to cortical bone present in the pathway of teeth, which are specifically to be moved creates transient osteopenia. This reduces the density of the cortical bone, hence speeding up the rate of orthodontic tooth movement. Many techniques have been implemented and perfected to enhance orthodontic tooth movement and shorten the treatment time in the literature. MOPs have proven to be a universally applied, nontechnical, repeatable, and minimally invasive method of accelerating tooth movement, with extremely minimal consequences.